Erosion control ecosystem service provided by Salix acutifolia Willd. Neophyte on the South Baltic coast: Insights from Wolin Island, Poland - Borysiak, Janina; Czyryca, Paweł; Stępniewska, Małgorzata (Quaestiones Geographicae, 2024)
Further global warming is projected to increase coastal erosion. Therefore, coastal protection is being intensified with a strong emphasis placed on environmental biotechniques. One such activity is anti-erosion planting using alien plant species. The aliens penetrate from the plant species into the natural ecosystems, reducing their biodiversity and ecosystem services. Parallel to coastal protection, measures for nature conservation are undertaken to eliminate invasive aliens from the natural ecosystems that take over. Such actions are featured in the master plans drafted for the Natura 2000 sites on the south Baltic coast. Although there is no sufficient scientific evidence, Salix acutifolia willow used in anti-erosion plantings was considered a neophyte invading white and grey dune habitats and reducing their biodiversity. The master plans mandated the elimination of the willow without considering the role of its spontaneous locations in providing erosion-control services. In 2017–2023, research was undertaken on the south Baltic coast (Wolin Island) on the arguments behind such a radical conservation action. We present the results of these studies. We consider the elimination of S. acutifolia from its spontaneous locations as a reduction in both its erosion-control services and the willow’s role in nature conservation. We present some principles for action in case of a conflict between coast protection and nature conservation.